Cohort profile: the European Unified Registries On Heart Care Evaluation and Randomized Trials (EuroHeart)—acute coronary syndrome and percutaneous coronary intervention - Bhatty, Asad; Wilkinson, Chris; Batra, Gorav; Alfredsson, Joakim; Erlinge, David; Ferreira, Jorge; Guðmundsdóttir, Ingibjörg J; Hrafnkelsdóttir, þórdís Jóna; Ingimarsdóttir, Inga Jóna; Irs, Alar; Járai, Zoltán; Jánosi, András; et al. (European Heart Journal - Quality of Care and Clinical Outcomes, 2024)
Abstract Aims The European Unified Registries On Heart Care Evaluation and Randomized Trials (EuroHeart) aims to improve the quality of care and clinical outcomes for patients with cardiovascular disease. The collaboration of acute coronary syndrome/percutaneous coronary intervention (ACS/PCI) registries is operational in seven vanguard European Society of Cardiology member countries. Methods and results Adults admitted to hospitals with ST-elevation myocardial infarction (STEMI) and non-ST-elevation myocardial infarction (NSTEMI) are included, and individual patient-level data collected and aligned according to the internationally agreed EuroHeart data standards for ACS/PCI. The registries provide up to 155 variables spanning patient demographics and clinical characteristics, in-hospital care, in-hospital outcomes, and discharge medications. After performing statistical analyses on patient data, participating countries transfer aggregated data to EuroHeart for international reporting. Between 1st January 2022 and 31st December 2022, 40 021 admissions (STEMI 46.7%, NSTEMI 53.3%) were recorded from 192 hospitals in the seven vanguard countries: Estonia, Hungary, Iceland, Portugal, Romania, Singapore, and Sweden. The mean age for the cohort was 67.9 (standard deviation 12.6) years, and it included 12 628 (31.6%) women. Conclusion The EuroHeart collaboration of ACS/PCI registries prospectively collects and analyses individual data for ACS and PCI at a national level, after which aggregated results are transferred to the EuroHeart Data Science Centre. The collaboration will expand to other countries and provide continuous insights into the provision of clinical care and outcomes for patients with ACS and undergoing PCI. It will serve as a unique international platform for quality improvement, observational research, and registry-based clinical trials.